Pariwisata dan Identitas Perempuan Banjar: Suatu Analisis Sosiologi dalam Cerpen Gadis Pasar Terapung - Setia Budhi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2023)
This article is about the identity of Banjar women in South Kaliantan in literary works. Literary studies on tourism have not been studied much. A qualitative study on the case of the short story